"TRAVELING RUBOI" FROM THE POINT OF VIEW OF HOYAMISTS (International Conference on Economics, Finance, Banking and Management, 2025)
The term "wandering ruboi" is used in literary studies to refer to the ruboi of Umar Khayyam. Umar Khayyam (1048-1131) was a famous medieval Persian — Tajik poet, scholar and philosopher whose ruboists are considered masterpieces of literature around the world. A " ruboi "(Arabic for" four") is a form of poetry consisting of four verses, usually of philosophical, moral, or romantic content.